Clinical relevance of 3D gait analysis in patients with haemophilia. Issue 5 (10th July 2018) - Fouasson‐Chailloux, A.; Maugars, Y.; Vinatier, C.; Trossaert, M.; Menu, P.; Rannou, F.; Guicheux, J.; Dauty, M.
Abstract : Haemophilia is characterized by a congenital deficiency of clotting factor VIII or IX. One of the consequences of haemophilia is joint bleedings. Repetitive haemathroses induce cartilage damage and chronic synovitis leading to joint deterioration, and to definitive haemophilic arthropathy which is source of walking disability. Three‐dimension gait analysis (3DGA) appears particularly relevant in the case of haemophilia because it allows an evaluation of several joints in weight‐bearing situations. The purpose of this study was to review the interest and the contribution of 3DGA in the management of patients with haemophilia. The greatest interest of gait analysis would be to detect early walking changes with a non‐invasive and well‐tolerated examination, especially in paediatric population. In adulthood, this technic may be also useful to help detect walking worsening in patients known to have already arthropathy. However, it takes time to realize and needs expensive equipment, which limits its possibility of routine use. Although generalizations of these results remain difficult, especially to compare patients with haemophilia to normal population. Indeed, in the studies, patient groups are small and usually heterogeneous in terms of age and target joints. It certainly results of the rarity of the disease. So, it could be interesting to perform a study with a larger cohort in order to allow subgroup analysis, helping to define clearly the place of 3DGA in the strategy of haemophilia evaluation.